Kritik atas Pemahaman Kaum Feminis terhadap Otoritas Mufasir Laki-laki - Taufik Apandi (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2015)
The spread of the feminist movement in the West has forced women to rebel against a system that is considered culturally and structurally discredit their existence. When feminism entered into Islam, this movement has a significant impact and tends to destructive. Through feminist theology, teachings that have been established but it is considered contrary to the spirit of equality will be sued. Feminist theologians questioned some of the teachings of Islam that has been established, such as the interpretation of the Qur’an made by the mufasir because of potential gender bias. The reason is, when the man interprets the Qur’an, the women feeling excluded and the more dominant maleness is the nature and importance. Strangely, they do not mind at all when there are feminist activists from among men. View suspicious of mufasir is certainly wrong. Because the interpretation procedure under consideration is not sex but a quality of faith and science commentators. In addition, the tradition of criticism, will narrow the emergence of interpretations are oriented to personal interests and discredit women. Whereas the interpretations results of mufassir actually much glory to women. Therefore efforts feminist theologians sue mufassir actually is not a scientific claim usually done in a scientific study, but an attempt of shari’ah deconstruction for Muslim women who want to follow in the footsteps of West women.